2020
DOI: 10.1002/adtp.202000044
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Immune Response against Metastatic Tumors via Vaccination of Mannan‐BAM, TLR Ligands, and Anti‐CD40 Antibody (MBTA)

Abstract: Emerging evidence is demonstrating the extent of T‐cell infiltration within the tumor microenvironment has favorable prognostic and therapeutic implications. Hence, immunotherapeutic strategies that augment the T‐cell signature of tumors hold promising therapeutic potential. Recently, immunotherapy based on intratumoral injection of mannan‐BAM, toll‐like receptor ligands and anti‐CD40 antibody (MBTA) demonstrated promising potential to modulate the immune phenotype of injected tumors. The strategy promotes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…Several studies have established that constituents of MBTA immunotherapy result in a substantial response in murine subcutaneous tumors including melanoma, sarcoma, pancreatic adenocarcinoma, and pheochromocytoma [ 1 , 2 , 4 , 7 , 23 , 33 ]. One of these studies demonstrated the significant reduction in tumor volume and increased overall survival in a mouse model of metastatic pheochromocytoma treated with intratumoral mannan-BAM and TLR ligands (MBT) injection [ 1 , 2 ].…”
Section: Preclinical Investigations Of Mbta Immunotherapy In Oncolmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have established that constituents of MBTA immunotherapy result in a substantial response in murine subcutaneous tumors including melanoma, sarcoma, pancreatic adenocarcinoma, and pheochromocytoma [ 1 , 2 , 4 , 7 , 23 , 33 ]. One of these studies demonstrated the significant reduction in tumor volume and increased overall survival in a mouse model of metastatic pheochromocytoma treated with intratumoral mannan-BAM and TLR ligands (MBT) injection [ 1 , 2 ].…”
Section: Preclinical Investigations Of Mbta Immunotherapy In Oncolmentioning
confidence: 99%
“…Further, in our previous MBTA study using a murine colon carcinoma CT26 cell line, we demonstrated that intratumoral injection of MBTA as well as subcutaneous delivery of a vaccine consisting of irradiated autologous, whole tumor cell pulsed with MBTA could induce a robust tumor-specific adaptive immune response [ 23 ]. Primary and metastatic representative tumors were established by CT26 tumor cell inoculation into the right and left flank, respectively [ 23 ]. Intratumoral injection of MBTA versus saline into the primary right flank tumor was administered according to the treatment schedule.…”
Section: Preclinical Investigations Of Mbta Immunotherapy In Oncolmentioning
confidence: 99%
See 3 more Smart Citations